If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-3x-3x=-4x(2x+7)
We move all terms to the left:
-3x-3x-(-4x(2x+7))=0
We add all the numbers together, and all the variables
-6x-(-4x(2x+7))=0
We calculate terms in parentheses: -(-4x(2x+7)), so:We get rid of parentheses
-4x(2x+7)
We multiply parentheses
-8x^2-28x
Back to the equation:
-(-8x^2-28x)
8x^2+28x-6x=0
We add all the numbers together, and all the variables
8x^2+22x=0
a = 8; b = 22; c = 0;
Δ = b2-4ac
Δ = 222-4·8·0
Δ = 484
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}$$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}$$\sqrt{\Delta}=\sqrt{484}=22$$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(22)-22}{2*8}=\frac{-44}{16} =-2+3/4 $$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(22)+22}{2*8}=\frac{0}{16} =0 $
| 4=2÷5g | | (2/5)y-5=-3 | | x=95-95x(15/100) | | 7×-6y-19=0 | | 0.5r-3=12-9.5r | | 8x−5=6x+9 | | X+2(x-5)=30 | | 3x+15+2x-5=90 | | -(n+4)=-36-5n | | 0.5r-3=12-9/2r | | 67=c+20 | | X²+4x+4=0 | | 2(g-5)-4=4 | | x-95=15 | | 100=10x+10E(-3x) | | 11-c=-10c= | | -6+7=2x | | d-30=27 | | 4x/16-3/8-x/16=3/16 | | X/3+8=19x= | | -(6x+6)+2=-6×-3 | | -(-5x-6)=18+7x | | h/6=5 | | -(-6x-6)=18+7x | | 45=z-50 | | 3=p+2 | | 84=v-66 | | 6a-2=4a+4 | | -68-m=91 | | 19=w+-67 | | 62=y+43 | | 10=a/5-3 |